Predictors of the extent and severity of coronary artery disease for prognosis of patients with non-ST-segment elevation acute coronary syndromes - Chirag Patel; Jayesh Prajapati; Iva V Patel; Roopesh Singhal; Ashish Mishra; Gaurav Singh (Publisher: Shahid Beheshti University of Medical Sciences, 2018)
Introduction: The proportion of patients visiting emergency department with chest pain indicative of non‐ST‐segment elevation acute coronary syndrome (NSTE-ACS) is increasing. The current risk assessment of patients with NSTE-ACS may calculate patients risk for recurrent events but may fail to identify patients with severe coronary artery disease (CAD). The present study aimed to identify predictors of the extent and severity of CAD for prognosis of NSTE-ACS patients undergoing early angiography.Methods: A total of 215 patients with NSTE-ACS were enrolled randomly and followed up between April-2015 and February-2017 at a tertiary healthcare center. The coronary angiography was performed. Patients were divided into two groups: high-risk coronary anatomy (HRCA) and low-risk coronary anatomy (LRCA). Patients were analyzed for baseline, demographic, clinical characteristics, and cardiovascular risk factors, during hospitalization and 30 days post discharge.Results: Among 215 enrolled patients, 90 (mean age: 52.22 ± 10.24 year) and 125 (mean age: 57.78 ± 8.83 year) patients were in the LRCA and HRCA group, respectively. The presence of previous heart failure [Odds Ratio (OR): 3.95, 95% confidence interval (CI): 1.11-14.10; P = 0.03], chronic renal failure [OR: 5.11, 95% CI: 1.12-23.22; P = 0.03] and peripheral vascular disease [OR: 3.38, 95% CI: 1.09-10.42; P = 0.03] were significant independent predictors of HRCA. Additionally, Grace score >140 was the significant predictor of 30 days mortality [OR: 5.85; P = 0.02] and major adverse cardiac and cerebral events [MACCE; OR: 6.23, 95% CI: 2.22-17.50; P = 0.001].Conclusions: The extent and severity of CAD in NSTE-ACS patients can be predicted by assessing HRCA through clinical parameters. However, the correlation of HRCA with 30 days MACCE and mortality was modest